Respuesta :

Duplicating Polynomials. To duplicate two polynomials, you apply the distributive property . Think about a straightforward model: duplicating a monomial 3x by the binomial x−2 . When you increase one binomial by another binomial, you need to utilize the distributive property over and again.

For this case we have that by definition, the distributive property establishes that:

[tex](a + b) (c + d) = ac + ad + bc + bd[/tex]

If we have two polynomials of the form:

[tex]P (x) = ax ^ 2 + x\\G (x) = x + 3[/tex]

To multiply we apply the definition of distributive property, having that to multiply powers of the same base, the same base is placed and the exponents are added.

[tex]P (x) * g (x) = (ax ^ 2 + x) (x + 3) = ax ^ 3 + 3ax ^ 2 + x ^ 2 + 3x[/tex]

Answer:

[tex](a + b) (c + d) = ac + ad + bc + bd[/tex]

ACCESS MORE